Pengaruh Perilaku Konsumen, Brand Loyalty, Dan Experiental Marketing, Terhadap Keputusan Pembelian (Studi Kasus Konsumen Mixue di Kota Mojokerto) - Al-Baihaqi, Mochammad Amiruddin; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study was conducted to determine the effect of Consumer Behaviour, Brand Loyalty, Experiental Marketing on purchasing decisions for mixue ice cream & tea products in Mojokerto City. This research method uses quantitative methods using non-probability sampling techniques and the data source used is primary data with data collection using a Likert scale questionnaire to consumers who have purchased mixue ice cream & tea in Mojokerto city. The calculation sample in this study used the Malhotra formula which resulted in 90 respondents. The data analysis used is descriptive analysis, instrument test, classical assumptions, multiple linear regression analysis and hypothesis testing using the help of SPSS 25 for Windows. The results of this study indicate that Consumer Behaviour, Brand Loyalty and Experiental Marketing simultaneously influence the decision to purchase mixue ice cream & tea products in Mojokerto city. Partially, Consumer Behaviour and Brand Loyalty have a significant positive effect but Experiental Marketing has a positive and insignificant effect on purchasing decisions for mixue ice cream & tea products in Mojokerto city. Keywords: Consumer Behaviour, Brand Loyalty, Experiental Marketing And Purchasing Decisions.